Diagnostic efficacy of fasting insulin-to-C-peptide ratio in exogenous insulin autoimmune syndrome - Han, Tuo; Wang, Ziyue; Zhou, Jing; Zhang, Nenghan; Li, Jiajun; Feng, Na; Guo, Chen; Zhang, Wenqian; Li, Yongqin; Wu, Juanjuan; Zhang, Chunyan; Zhang, Yan (Frontiers in Medicine, 2026)
BackgroundThe early-stage diagnosis of exogenous insulin autoimmune syndrome (EIAS) remains a significant clinical challenge for endocrinologists. This study aimed to investigate the diagnostic predictive utility of the fasting insulin-to-C-peptide ratio in EIAS.MethodsDiabetic patients with insulin autoantibody (IAA) testing admitted to our hospital between June 2023 and March 2024 were retrospectively enrolled. Participants were stratified into control and EIAS groups based on IAA status. A comparative analysis of EIAS clinical features was performed, with receiver operating characteristic (ROC) curve analysis used to determine the predictive efficacy of the fasting insulin/C-peptide ratio for EIAS.ResultsAmong 120 enrolled diabetic patients with IAA testing, 37 (30.8%) fulfilled the EIAS diagnostic criteria. Compared with patients in the control group, patients in the EIAS group were significantly older and had a longer duration of diabetes, demonstrated greater use of aspart insulin and recombinant human insulin formulations, and required higher insulin dosages. The EIAS cohort exhibited lower fasting glucose and HbA1c levels, alongside markedly elevated fasting and 2-h postprandial insulin concentrations and increased HOMA-IR values. ROC analysis established the fasting insulin/C-peptide ratio as a moderately accurate predictor of EIAS (AUC 0.802; 95% CI 0.724–0.880), with an optimal diagnostic threshold of 5.215 μU/ng providing 78.4% sensitivity and 77.1% specificity.ConclusionAdvanced age, prolonged diabetes duration, elevated insulin dosage requirements, recurrent hypoglycemia, and hyperinsulinemia constitute characteristic clinical features of EIAS. The fasting insulin/C-peptide ratio demonstrated favorable diagnostic performance, positioning it as a practical screening biomarker for EIAS.